Clinical pharmacist interventions in the transition of care in a mental health hospital: case reports focused on the medication reconciliation process - Stuhec, Matej; Batinic, Borjanka (Frontiers in Psychiatry, 2023)
The transition of care represents a key point in the hospital admission and discharge process. A comprehensive transition could lead to fewer medication-related problems. The hospital clinical pharmacist could help in the transition of care process with a comprehensive medication reconciliation process, which has been poorly described in mental health hospitals. This study presents two clinical cases in which hospital clinical pharmacists identified omitted medications and other medication-related issues, including medication errors, during the transition of care in a mental health hospital. These positive experiences may encourage other countries to establish similar collaborations with hospital clinical pharmacists in mental health hospitals.